1995
DOI: 10.1093/wber/9.3.397
|View full text |Cite
|
Sign up to set email alerts
|

Political Influence on the Central Bank: International Evidence

Abstract: Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in der dort genannten Lizenz ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
95
0
4

Year Published

1998
1998
2015
2015

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 223 publications
(104 citation statements)
references
References 8 publications
2
95
0
4
Order By: Relevance
“…Cukierman, Webb, and Neyapti (1992) argue that high turnover of central bank governors is indicative of low independence, and they show that the rate of turnover is positively and significantly correlated with inflation in a sample including both developed and developing countries. 17 Cukierman and Webb (1995) collect data on the frequency with which central bank governors are replaced in the six months following changes in government, a period where any political influence is most likely to be exercised. We use this latter measure, which we call governor turnover, in our test of hypothesis 3, because it appears to be the best available proxy for the extent of political interference with central bank governors.…”
Section: Datamentioning
confidence: 99%
“…Cukierman, Webb, and Neyapti (1992) argue that high turnover of central bank governors is indicative of low independence, and they show that the rate of turnover is positively and significantly correlated with inflation in a sample including both developed and developing countries. 17 Cukierman and Webb (1995) collect data on the frequency with which central bank governors are replaced in the six months following changes in government, a period where any political influence is most likely to be exercised. We use this latter measure, which we call governor turnover, in our test of hypothesis 3, because it appears to be the best available proxy for the extent of political interference with central bank governors.…”
Section: Datamentioning
confidence: 99%
“…However, in an unstable political regime where power changes occur irregularly through extra-constitutional means, like coups, the incumbent may be preoccupied with his own survival and decide to keep all levers of policy, including monetary in his own hands. These questions are further investigated in the works of Cukierman and Webb (1995), De Haan and Van't Hag (1995), Bagheri and Habibi (1998), Moser (1999) and Keefer and Stasavage (2003).…”
Section: Conflicts Of Interests Political Insurance and Independencementioning
confidence: 99%
“…) recognise that a low turnover does not necessarily mean that the central bank is more independent, as a governor who tows the government line may stay longer in office. The issue of how likely it is that a CB governor will be replaced after a change in government is further studied in Cukierman and Webb (1995 Table 2 it is observed that the correlation coefficient for the De Jure JI and legal CBI indices is statistically insignificant implying the lack of the presumed positive association between those two variables (first row of the Table). The theoretical prediction of legal JI and CBI complementarity based on the intuitive arguments of Goodhart (2002) and Salzberger and Voigt (2002) is rejected by the data.…”
Section: Control Of Policy Instrumentsmentioning
confidence: 99%
“…Despite de jure independence, central banks in developing countries are often subject to informal channels of political influence from the financial community and to high staff turnover, which in practice limit their operational autonomy (see Cukierman & Webb, 1995;Cukierman, Webb, & Neyapti, 1992). In many developing and transitional countries, interlocking elites in government and the private sector can sway central bank decisions in their favor.…”
Section: (A) Participation Issuesmentioning
confidence: 99%